Talking about ethics : a conversational approach to moral dilemmas - Jones, Michael S., 1964-; Farnham, Mark J.; Saxon, David L. (Kregel Academic, 2021)
"An accessible introduction to ethics through engaging dialoguesTalking About Ethics provides the reader with all of the tools necessary to develop a coherent approach to ethical decision making. Using the tools of ethical theory, the authors show how these theories play out in relation to a wide variety of ethical questions using an accessible dialogue format. The chapters follow three college students as they discuss today's most important ethical issues with their families and friends, including: Immigration, Capital punishment, Legalization of narcotics, Abortion, Premarital sex, Reproductive technologies, Gender identity, The environment, and many more. The engaging dialogue format illustrates how these topics often take shape in the real world, and model critical thinking and Christian ethical decision making. Study aids in each chapter include overviews, sidebars, reflection questions, glossaries, and recommended reading."--Publisher